INFLUENCE OF INFLATION RATE ON MACHINERY HIRE RATES IN CONSTRUCTION INDUSTRY - Salah Alaloul, Wesam; Musarat, Muhammad Ali; Liew, M. S.; Qureshi, Abdul Hannan (Journal of Civil Engineering, Science and Technology, 2021)
Cost overrun is encountered in various construction projects and even with various advancement, the issue remains. When cost overrun occurs in any construction project, it not only affects the project also leaves marks on the construction industry as well. Machinery hire rates are important while finalizing the project budget and when the rates change annually it may result in project cost overrun. Due to these facts, this study investigates the effect of inflation rate on machinery hire rates. Inflation is a powerful influencing factor in deviating the prices and the rates which result in cost overrun. Statistical analysis was performed where the Spearman correlation was used as the data possess a nonlinear behaviour. The overall result came significant as the inflation rate showed a strong relationship with 9 machinery hire rates demonstrating that the inflation rate is the most prominent factor in deviating the rates. Three (3) machinery hire rates showed a moderate relationship, whereas 1 showed a weak relationship with the inflation rate. Therefore, a consideration of the inflation rate should be made in budget estimation.